Informative Certification: Screening vs. Acquisition - Celik Gorkem; Roland Strausz (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2025)
We study monopolistic certification in a buyer-seller relationship, explicitly distinguishing between its role as a device for screening versus acquisition. As a screening device, certification discloses soft information about a seller's private information. As an acquistion device, certification discloses hard information about the good's quality. Despite being costless, we show that, optimally, a monopolistic certifier provides non-maximal information-acquisition, while offering maximal screening. Thus, monopolistic certification exhibits no economic distortions as a screening device, resolving all private information, but provides too little hard information as an acquisition device. While feasible and costless, full information acquisition is suboptimal as it requires excessive information rents. Consequently, market inefficiencies remain due to market uncertainty but not due to private information.
Keywords: D82; 330; certification; disclosure; screening; information acquisition; monopolistic distortions